Public perception and perceived landscape function of urban park trees in Tabriz, Iran - Hami, Ahmad; Maruthaveeran, Sreetheran (International Association for Landscape Ecology, Chapter Germany, 2018)
Landscapes of parks may contribute an important function in the urban park with a wide range of benefits. However, there is a lack of understanding of the publics‘ preferences for parks‘ landscape funtions and benefits in middle-east countries such as Iran. About 275 park users were interviewed using photo-questionnaire in Tabriz, Iran using five point Likert scale (1 = strongly disagree,.. 5 = strongly agree) for measuring their preference level. Descriptive analysis, factor analysis, and variance analysis (Independent sample t-test and ANOVA) were used for analyzing the data. The results revealed the majority of the participants were male (54.5%), single (65.09%), highly educated (71.4%), below 40 years old (62.9%), and visit the park with family members (43.3%) in the evenings (54.5%). The participants preferred the presence of Salix alba followed by Pinus nigra, Platanus occidentalis, and Morus alba in the urban park, respectively. “Flowering purpose“ (mean= 4.21) and “green enlargement“ (mean= 4.20) were important functional dimensions, whilst, “health care“ (mean= 4.33) and “mental recovery“ (mean= 4.29) landscape benefits in urban parks. It is concluded that, perhaps, attributions of trees such as creating shade, with the canopy on top, and having large leaves are significant factors on publics‘ landscape preferences.